A biofunctionalizable ink platform composed of catechol-modified chitosan and reduced graphene oxide/platinum nanocomposite - Sobolewski, Peter; Goszczyńska, Agata; Aleksandrzak, Małgorzata; Urbaś, Karolina; Derkowska, Joanna; Bartoszewska, Agnieszka; Podolski, Jacek; Mijowska, Ewa; El Fray, Mirosława (Beilstein Journal of Nanotechnology, 2017)
We present an ink platform for a printable polymer–graphene nanocomposite that is intended for the development of modular biosensors. The ink consists of catechol-modified chitosan and reduced graphene oxide decorated with platinum nanoparticles (rGO–Pt). We modified the chitosan with catechol groups, in order to obtain adhesive properties and improve solubility. Dispersions of rGO–Pt in ethylene glycol were admixed with an aqueous solution of modified chitosan to yield an ink that is suitable for non-contact piezoelectric printing using a commercial microplotter (Sonoplot GIX Microplotter Desktop). As a proof of concept, printed patterns were biofunctionalized with DNA oligonucleotide probes for Streptococcus agalactiae (Group B streptococcus) using glutaraldehyde as a linker. Confocal microscopy revealed the successful hybridization of complementary polymerase chain reaction (PCR) products and low non-specific binding. Our results demonstrate that catechol-modified chitosan/rGO–Pt nanocomposites can be used as inks for piezoelectric printing and facilitate the attachment of biorecognition elements for biosensor applications.
Keywords: biosensing; catechol; chitosan; graphene; piezoelectric printing

(untitled) - Bellan, L. M.; Wu, D.; Langer, R. S. (Wiley Interdiscip. Rev.: Nanomed. Nanobiotechnol., 2011)

(untitled) - Novoselov, K. S.; Geim, A. K.; Morozov, S. V.; Jiang, D.; Zhang, Y.; Dubonos, S. V.; Grigorieva, I. V.; Firsov, A. A. (Science, 2004)

(untitled) - Pumera, M. (Mater. Today, 2011)

(untitled) - Sobolewski, P.; Piwowarczyk, M.; El Fray, M. (Macromol. Biosci., 2016)

(untitled) - Dias, A. D.; Kingsley, D. M.; Corr, D. T. (Biosensors, 2014)

(untitled) - Li, J.; Rossignol, F.; Macdonald, J. (Lab Chip, 2015)

(untitled) - Larson, B. J.; Gillmor, S. D.; Lagally, M. G. (Rev. Sci. Instrum., 2004)

(untitled) - Dash, M.; Chiellini, F.; Ottenbrite, R. M.; Chiellini, E. (Prog. Polym. Sci., 2011)

(untitled) - Kim, K.; Ryu, J. H.; Lee, D. Y.; Lee, H. (Biomater. Sci., 2013)

(untitled) - Sedó, J.; Saiz-Poseu, J.; Busqué, F.; Ruiz-Molina, D. (Adv. Mater., 2013)

(untitled) - Johnson, D. W.; Dobson, B. P.; Coleman, K. S. (Curr. Opin. Colloid Interface Sci., 2015)

(untitled) - Torrisi, F.; Hasan, T.; Wu, W.; Sun, Z.; Lombardo, A.; Kulmala, T. S.; Hsieh, G.-W.; Jung, S.; Bonaccorso, F.; Paul, P. J.; Chu, D.; Ferrari, A. C. (ACS Nano, 2012)

(untitled) - Park, J.; Moon, J. (Langmuir, 2006)

(untitled) - Jang, D.; Kim, D.; Moon, J. (Langmuir, 2009)

(untitled) - Singh, A.; Sinsinbar, G.; Choudhary, M.; Kumar, V.; Pasricha, R.; Verma, H. N.; Singh, S. P.; Arora, K. (Sens. Actuators, B, 2013)

(untitled) - Mansouri, S.; Lavigne, P.; Corsi, K.; Benderdour, M.; Beaumont, E.; Fernandes, J. C. (Eur. J. Pharm. Biopharm., 2004)

(untitled) - Rivet, C.; Lee, H.; Hirsch, A.; Hamilton, S.; Lu, H. (Chem. Eng. Sci., 2011)

(untitled) - Ma, P. L.; Lavertu, M.; Winnik, F. M.; Buschmann, M. D. (Biomacromolecules, 2009)

(untitled) - Marcano, D. C.; Kosynkin, D. V.; Berlin, J. M.; Sinitskii, A.; Sun, Z.; Slesarev, A.; Alemany, L. B.; Lu, W.; Tour, J. M. (ACS Nano, 2010)

(untitled) - Wojtoniszak, M.; Chen, X.; Kalenczuk, R. J.; Wajda, A.; Łapczuk, J.; Kurzewski, M.; Drozdzik, M.; Chu, P. K.; Borowiak-Palen, E. (Colloids Surf., B, 2012)

(untitled) - Ayán-Varela, M.; Paredes, J. I.; Villar-Rodil, S.; Rozada, R.; Martínez-Alonso, A.; Tascón, J. M. D. (Carbon, 2014)

(untitled) - Schindelin, J.; Arganda-Carreras, I.; Frise, E.; Kaynig, V.; Longair, M.; Pietzsch, T.; Preibisch, S.; Rueden, C.; Saalfeld, S.; Schmid, B.; Tinevez, J.-Y.; White, D. J.; et al. (Nat. Methods, 2012)

Challenges and approaches for particle size analysis on micrographs of nanoparticles loaded onto textile surfaces - Underwood, S. J.; Gorham, J. M. (National Institute of Standards and Technology, 2017)